2020
DOI: 10.15585/mmwr.mm6941a3
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics, Experiences, and Beliefs Associated with Hand Hygiene Among Adults During the COVID-19 Pandemic — United States, June 24–30, 2020

Abstract: Frequent hand hygiene, including handwashing with soap and water or using a hand sanitizer containing ≥60% alcohol when soap and water are not readily available, is one of several critical prevention measures recommended to reduce the spread of SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID-19).* Previous studies identified demographic factors associated with handwashing among U.S. adults during the COVID-19 pandemic (1,2); however, demographic factors associated with hand sanitizing and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 10 publications
9
45
3
Order By: Relevance
“…Frequent handwashing has been found to be associated with decreased risk of infection with SARS-CoV-2, 18 therefore it is critical to identify strategies to promote this behavior among people with disabilities who, may be at increased risk for severe illness from COVID-19 because of higher prevalence of underlying conditions. Several of the factors associated with hygiene compliance among different demographic groups (gender, age, race/ethnicity, education, and household income) were consistent with work conducted among general populations which have been reported during the COVID-19 pandemic 19 , 20 , 21 and during previous respiratory pandemics. 22 Additional work is needed to further examine demographic factors associated with hygiene-related behavior among different disability types during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 81%
“…Frequent handwashing has been found to be associated with decreased risk of infection with SARS-CoV-2, 18 therefore it is critical to identify strategies to promote this behavior among people with disabilities who, may be at increased risk for severe illness from COVID-19 because of higher prevalence of underlying conditions. Several of the factors associated with hygiene compliance among different demographic groups (gender, age, race/ethnicity, education, and household income) were consistent with work conducted among general populations which have been reported during the COVID-19 pandemic 19 , 20 , 21 and during previous respiratory pandemics. 22 Additional work is needed to further examine demographic factors associated with hygiene-related behavior among different disability types during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies have indicated that risk awareness (e.g., having a close friend or relative who tested positive for SARS-CoV-2) was found to motivate more frequent effort in cleaning and disinfecting surfaces 6 and engagement in hand hygiene. 28 Similarly, increasing risk awareness specifically regarding unsafe cleaning and disinfection practices may increase adoption of safety precautions, as low risk perception may motivate lack of adherence to safety precautions. Prevention messages that describe examples of adverse health outcomes experienced by individuals who engaged in unsafe use or storage of cleaners, disinfectants, and hand sanitizers may be effective and should be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The stress from the pandemic and physical distancing is expected to increase both mental health symptoms and substance use, particularly among those already vulnerable to these conditions (Du et al 2020 ; McKay and Asmundson 2020 ). Emerging data (Czeisler et al 2020 ; McKay and Asmundson 2020 ) and anecdotal reports on implementation support calls support this concern. Additionally, those with substance use disorders have higher rates of the comorbid health conditions that increase vulnerability to the impacts of COVID-19 (Farhoudian et al 2020 ; Volkow 2020 ).…”
Section: Case Study: Integrated Treatment Initiativementioning
confidence: 99%